Confessions of an Impotent Potentate: Reading Daniel 4 through the Lens of Ritual Punishment Theory - Cason, Thomas Scott (Journal for the study of the Old Testament, 2014)
This article offers a rereading of Dan. 4.30 through the lens of a male punishment ritual. It is argued that the punishments God inflicts on Nebuchadnezzar reflect aspects found in a liminal hazing rite. Indeed, one of the primary markers of hazing is the use of sexual degradation as a means to establish the hierarchical division between initiator and initiated. The images found in Dan. 4.30 symbolize the dramatic collapse of Nebuchadnezzar's masculinity as he is made aware of his subordinate place in the universe. To make the case, recent insights from cultural anthropologists regarding male punishment rituals are incorporated. As sexual degradation is a telltale feature within hazing incidents, psychoanalytic criticism and gender criticism help elucidate how Nebuchadnezzar's compulsory embodiment of an animalized existence impacts his masculine identification in the narrative. Finally, it is noted that gender readings of the book of Daniel are few and far between, largely due to the absence of female characters in the book. By framing Daniel 4 within the context of competing masculinities, it is hoped that scholars interested in gender readings of the Bible will be provided with another lens through which to analyze this document.